ANALISIS KINERJA SISTEM PENYEDIAAN AIR MINUM DITINJAU DARI KAPASITAS INTAKE, KEBUTUHAN AIR PELANGGAN, DAN EFISIENSI DISTRIBUSI AIR BERSIH - Ahmad Ali Kumail; Achmad Syarifuddin (CV. KAMPUS AKADEMIK PUBLISING, 2026)
An evaluation of the drinking water supply system is necessary to ensure the fulfillment of community water needs and the operational sustainability of clean water services. This study examines the performance of the clean water distribution system of the Lalan Branch through an analysis of intake capacity, customer water demand, and distribution efficiency using operational data from August 2025. The actual intake capacity was recorded at 12,816 m³/month, with a maximum potential of 19,224 m³/month. Water distribution amounted to 9,468 m³/month, while measured customer consumption was 9,105 m³/month. Based on SNI standards, customer demand is 6,264.48 m³/month. The difference between production and distribution results in an NRW value of 26.1% (3,348 m³/month), influenced by the backwash process and technical network losses. The findings indicate that intake capacity is sufficient to meet customer demand, but distribution efficiency still needs to be improved.